Microwave Assisted Heterocyclization: A Rapid and Efficient Synthesis and Antibacterial Activity of Novel Thiazolidinones - B. D. Naik; K. R. Desai (E-Journal of Chemistry)
As a target to synthesize various Thiazolidinone derivatives, 2-Amino-4-(coumarin-3-yl)-thiazole has been prepared by the reactions of 3-Bromo acetyl coumarin with thiourea. 3-Bromo acetyl coumarin was prepared from 3-Acetyl coumarin. The resulting compound 2-amino-4-(coumarin-3-yl)- thiazole was treated with different Aldehydes to give the intermediate Schiff base, which on further reaction with Thioglycolic acid and Thiolactic acid to give titled compound Thiazolidinone. The structures of the compounds have been confirmed by elemental analysis and spectral analysis. The antibacterial activity of the compounds has also been screened against Staphylococcus aureus and Escherichia coil.